Low- and high-cocaine intake affects the spatial and temporal dynamics of class IIa HDAC expression-activity in the nucleus accumbens and hippocampus of male rats as measured by [18F]TFAHA PET/CT neuroimaging - Shane A. Perrine; Walid F. Alsharif; Arman Harutyunyan; Swatabdi Kamal; Nerissa T. Viola; Juri G. Gelovani (Addiction Neuroscience, 2022)
Repeated cocaine alters neuronal function in the nucleus accumbens (NAc), a brain region involved in cocaine taking, and in hippocampus (HC), known for contextual and associative learning. [18F]TFAHA is a histone deacetylase (HDAC) class IIa-specific radiotracer for positron emission tomography (PET)-imaging developed by our group to study epigenetic mechanisms. Here, [18F]TFAHA was used to conduct PET-imaging coupled with computed tomography (CT) of rat brains at baseline and after repeated cocaine intravenous self-administration (cocaine-IVSA) in low-intake versus high-intake cocaine groups. A 3 h-access FR1-schedule of cocaine-IVSA (0.5 mg/kg/infusion) for 12 continuous days was used with male Sprague Dawley rats following jugular vein catheterization. PET/CT neuroimaging with [18F]TFAHA was acquired in a dynamic mode over 40 min post-radiotracer administration at baseline and on day 12 of cocaine-IVSA using a longitudinal, repeated design. This study shows that high-cocaine intake significantly decreases class IIa HDAC expression-activity in NAc, while low-cocaine intake significantly decreases expression-activity in HC in male rats. These findings suggest the individual rats with low-cocaine intake had epigenetic changes in HC, where drug-associative changes occur. Alternatively, individuals with high-cocaine intake had robust epigenetic changes in NAc, where rewared-related behaviors originate. These findings are the first longitudinal data obtained in vivo to implicate class IIa HDACs in the persistent behavioral effects of cocaine. Furthermore, our results are consistent with published research implicating class IIa HDACs in cocaine-induced brain changes and studies suggesting a relationship between an individual's drug-taking behavior and regional pattern of epigenetic changes in the brain.